Strategies to Increase Teacher Competency in Efforts to Generate Vocational School Graduates According to Standards of Business and Industry (DUDI) - Siregar , Dannerd Wilfried; Husen Saeful Insan; Sutaryat Trisnamansyah; Waska Warta (Islamicate Institute, 2019)
Competition in the Business and Industrial World (DUDI) is a part of which influences human life today and in the future. Its development was built by one of the human efforts in the field of education. SMK as an educational activity that prepares graduates to be ready for work is a fundamental thing, where work readiness itself will have an impact on life. SWOT theory includes Strengths, Weaknesses, Challenges and Threats which are the empirical principles put forward. With a qualitative method through the principles of observation, interview and documentation. Research Questions Focus on: 1. Teacher's Competency Strengths in developing graduates according to DUDI standards? 2. Weaknesses of Teacher Competence in developing graduates according to DUDI standards? 3. Teacher Competency Challenges in developing graduates who comply with DUDI standards? and 4. Threats of Teacher Competence in developing graduates according to DUDI standards? Where the results of the research show that the complexity of the standards of the business world and industry is very broad, while the implementation of teacher competencies has not been developed for the development of readiness to balance and develop DUDI itself.